2021
DOI: 10.3389/fonc.2021.649171
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 18F-DCFPyL PET/CT Imaging in Early Detection of Biochemically Recurrent Prostate Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: Prostate-specific membrane antigen (PSMA)-targeted 2-(3-{1-carboxy-5-[(6-[18F] fluoro-pyridine-3-carbonyl)-amino]-pentyl}-ureido)-pentanedioic acid (18F-DCFPyL) positron emission tomography/computed tomography (PET/CT) has shown advantages in primary staging, restaging, and metastasis detection of prostate cancer (PCa). However, little is known about the role of 18F-DCFPyL PET/CT in biochemically recurrent prostate cancer (BRPCa). Hence, we performed a systematic review and meta-analysis to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
(67 reference statements)
2
19
0
Order By: Relevance
“…Whereas other meta-analyses have investigated the diagnostic roles of tracers applied in PCa with BCR [ 2 , 6 , 7 , 78 , 79 ], to our knowledge, this is the first comparative meta-analysis that focuses on all three relevant tracers for the early detection of this disease. This meta-analysis showed a higher pooled DR for PCa with BCR using PSMA compared to that with fluciclovine and choline PET/CT for three PSA levels, and we observed a significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas other meta-analyses have investigated the diagnostic roles of tracers applied in PCa with BCR [ 2 , 6 , 7 , 78 , 79 ], to our knowledge, this is the first comparative meta-analysis that focuses on all three relevant tracers for the early detection of this disease. This meta-analysis showed a higher pooled DR for PCa with BCR using PSMA compared to that with fluciclovine and choline PET/CT for three PSA levels, and we observed a significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…To date, to our knowledge, this is the first evidence-based study to evaluate the DRs of 18 F-labeled and 68 Ga-labeled PSMA. Recently, there have been multiple meta-analyses showing that the summary DR of 18 F-labeled PSMA in patients with BCR was approximately 49% for PSA < 0.5 ng/mL [ 1 , 78 , 85 ], which is slightly better than the 44.9% detection rate of 68 Ga-PSMA in a recent prospective study [ 73 ]. Compared to 18 F-PSMA, 68 Ga-PSMA ligands have a short half-life (68 min), and thus are inconvenient for transport [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study comparing piflufolastat 18 F to a 68 Ga labeled PSMA compound revealed better sensitivity with an 18F-labeled compound [22]. A meta-analysis on piflufolastat 18 F accuracy in prostate cancer BCR revealed similar detection rates to this study’s analog PET/CT cohort [23].…”
Section: Discussionmentioning
confidence: 55%
“…In a performance evaluation of [ 18 F]DCFPyL PET/CT, in patients with recurrent PCa and low PSA levels, the detection rates were 63.6% (<0.2 ng/mL), 58.7% (0.2–0.49 ng/mL), 62.8% (0.5–0.99 ng/mL), 82.1% (1–1.99 ng/mL), and 91.7% (>2 ng/mL) [ 5 ], which were higher than for primary staging [ 90 ]. Recently, a meta-analysis reviewing the diagnostic performance of [ 18 F]DCFPyL in the early detection of BCR showed a pooled detection rate of 81% [ 93 ]. The author further stratified the detection rate by PSA values; the pooled detection rate was 88.8% for PSA values > 0.5 ng/mL and 47.2% for the PSA value < 0.5 ng/mL.…”
Section: Resultsmentioning
confidence: 99%